Grazing impact of the calanoid copepods Acartia spp. on the toxic dinoflagellate Alexandrium pseudogonyaulax in the western coastal waters of Korea - Lee, Moo Joon; Hwang, Yeong Jong; Choi, Yong Bum; Yoo, Yeong Du (Frontiers in Microbiology, 2024)
Marine dinoflagellate species in the genus Alexandrium are well known to produce paralytic shellfish poison as well as common coastal species with cosmopolitan distribution. However, few studies on the feeding of copepods on Alexandrium species have been conducted. The toxic dinoflagellate Alexandrium pseudogonyaulax contains goniodomin A and causes red tides in many countries. To investigate the relationship between the toxic dinoflagellate A. pseudogonyaulax and the calanoid copepod Acartia spp., we quantified the ingestion rates of Acartia spp. feeding on A. pseudogonyaulax as a function of prey concentration. Additionally, we estimated grazing coefficients by integrating data from field observations of Acartia spp. and coexisting A. pseudogonyaulax with laboratory measurements of ingestion rates obtained during this investigation. Furthermore, we compared the ingestion rates of Acartia spp. and other predators feeding on Alexandrium species as previously reported. The ingestion rates of Acartia spp. on A. pseudogonyaulax increased continuously with increasing mean prey concentration. The highest values among the ingestion rate of Acartia spp. feeding on A. pseudogonyaulax was 3,407 cells predator-1 d-1 (4,872 ng C predator-1 d-1) at the given prey concentration. The calculated grazing coefficients for Acartia spp. on A. pseudogonyaulax in Shiwha Bay, Korea, were up to 0.073 d-1. The results of this study suggest that A. pseudogonyaulax may decrease or maintain the population of Acartia spp. in marine food webs.